Tuberculosis thyroid with FNAC changes mimicking thyroid tumor - Tiwari, Neema; Gupta, Parul; Lal, Nirupma; Musa, Osman (Indian Journal of Case Reports, 2019)
TB in India is extremely common especially in young and adults as compare to other age groups. It is more common in the female population in India where women remain poor and neglected. We present the case of a 35-year-old male who presented with a thyroid lump. On examination, there was a solitary, non-tender, and firm swelling on the left midline neck with no evidence of lymphadenopathy. Ultrasound of thyroid revealed multinodular goiter with the largest nodule (3.5 × 2 cm) in the right lobe of the thyroid. Ultrasound-guided FNAC revealed follicular cells on a background of lymphocytes making a diagnosis of thyroiditis and underwent hemithyroidectomy for the same.